An unusual shaped Bronze Age logboat from the Starnberger See near the Roseninsel, Bavaria, Germany – an early evidence for push-rowing in Central Europe? - Weski, Timm (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
A logboat of 13.34 m length dendrodated to 900 BC was discovered in the Starnberger See. Most of its port side, the bow, and about two-thirds of the upper parts of the starboard side are missing. The prominent feature is a square balk protruding from the stern of unknown purpose. Further there are several auger holes, whose use cannot be explained. To show all these details a 3D documentation was necessary. Perhaps the logboat, which may have served as a ceremonial vessel, was rowed facing forward and not paddled.